Concentration and Behavioral Biases in the Active Management of BRIC Funds - Fasano, Antonio; Boido, Claudio (Ekonomika, 2017)
This study addresses two targets: first, the relationship between performance measurement and the focusing of fund investment strategies on local risk factors; second, the behavioral considerations which fall under this topic, in particular with regard to fund managers’ overconfidence. Brazil, Russia, India and China were supposed to represent a force of new demand growth and spending power, but the recent financial crisis in China (July and August 2015) and the former problems in the Russian economy, also caused by an embargo by other countries, have contributed to a shift which has occurred more quickly than expected. In this context, weak active management strategies, handicapped by behavioral biases, will be more evident and will cause more harm to the industry. Connections between these biases and the performance of funds are identified with the managers in charge, who are not only misguided by strong beliefs, but also take big bets on risky assets without producing significant alphas. To investigate the relationship between local bias and activism, we compare stock picking skills of local managers, the managing of domestic funds and non-local managers; therefore, we assume that local information can be exploited by a local manager with an active management strategy. It is also true that overconfident managers might be too focused on the specific stocks for which they believe to possess superior information. The results show that BRIC local managers are not closely tied to replication strategies of domestic indices and do not produce significant domestic alphas.